Características y riesgo obstétrico en adolescentes atendidas en el centro materno Perinatal – Tarapoto - Gonzales Flores, Lilia Antonieta (2001)
He was an epidemiological study of analytic description of cross-cutting, in order to determine what are the characteristics and risks of the adolescent gilt _: aged 19, served in the Perinatal Tarapoto maternal Centre, in the period Abril2000-March 2001. We used the information that are in the data bank of the system computer Perinatal births occurring in adolescent nulliparous women where they allocated all the corresponding to the mother, childbirth, puerperium and the newborn, the base, the data entry and analysis was performed using the software Epi info 6.04. Is recorded a total of 1708 births of which 508 were teenagers (29. 7%), 1096 ranged between 20-35 years (64.2%) and 104 older of 35 years (6.1%). This adolescent population 60% were gilt (305 cases), noting that 25% had no NPC. The variables with statistical significance were the marital status and the NPC (p < 0.05). The presence of obstetric pathology is...